Cerium oxide/polydimethylsiloxane polymer deposited onto tapered fiber for 1.97 µm mode-locked thulium-doped fiber laser - Ramli, Rizal; Mohd Yusoff, Norita; Mohamed Ahmed, Mahmoud Hazzaa; Mansor, Maisarah; Zainol Abidin, Nadiah Husseini; Ng, Eng Khoon; Alresheedi, Mohammed Thamer; Mahdi, Mohd Adzir (Elsevier, 2024)
This work presents the use of cerium oxide (CeO2) as saturable absorber (SA) in the mode-locked pulse fiber laser generation. The CeO2 materials were prepared through sonication which then incorporated into a polydimethylsiloxane (PDMS) polymer to be coated on a tapered fiber. The CeO2/PDMS-SA exhibited saturation intensity of 44 MW/cm2 and modulation depth of 3.4%, confirming its nonlinear intensity-dependent transmission characteristics. Integrated into a thulium-doped fiber laser cavity, the CeO2/PDMS-SA enabled mode-locking at a pump power of 420 mW, leading to a fundamental mode-locking operation up to 1484 mW within the net anomalous dispersion regime. The laser emitted pulses at wavelength of 1973 nm with signal-to-noise ratio of 54 dB, repetition rate of 9.04 MHz and pulse width of 1.49 ps. The CeO2/PDMS-SA mode-locked fiber laser demonstrated stability of an average 3 dB bandwidth of 2.89 ± 0.08 nm, average central wavelength of 1973.05 ± 0.14 nm and average pulse width of 1.5 ± 0.01 ps for the duration of 120 min. Notably, the CeO2/PDMS-SA demonstrated a high pulse energy of 10.62 nJ and average output power of 96 mW. This investigation suggests their viability for use in future studies. The results also demonstrated the potential of CeO2 for use in various photonics applications in the “eye-safe” region. © 2024 Elsevier B.V.